Effects of ACA Medicaid Expansions on Health Insurance Coverage and Labor Supply. (11th May 2017) - Kaestner, Robert; Garrett, Bowen; Chen, Jiajia; Gangopadhyaya, Anuj; Fleming, Caitlyn
Abstract: We examined the effect of the expansion of Medicaid eligibility under the Affordable Care Act on health insurance coverage and labor supply of low‐educated and low‐income adults. We found that the Medicaid expansions were associated with large increases in Medicaid coverage, for example, 50 percent among childless adults, and corresponding decreases in the proportion uninsured. There was relatively little change in private insurance coverage, although the expansions tended to decrease such coverage slightly. In terms of labor supply, estimates indicated that the Medicaid expansions had little effect on work effort despite the substantial changes in health insurance coverage. Most estimates suggested that the expansions increased work effort, although not significantly.